Social capital and students' health: results of the splash study. (13th November 2019) - Backhaus, I; Kawachi, I; Ramirez, A; Jang, S; Khoo, S; Al-Shamli, A; Po-Hsiu, L; Begotaraj, E; Fischer, F; Torre, G La
Abstract: Background: Universities around the world are challenged with rising rates of mental health problems among their students. Cumulative evidence demonstrated that aspects of the social environment, including social capital, play an important role in mental health. This study aimed to determine the prevalence of depressive symptoms among university students from across the globe and to investigate whether social capital was associated with depressive symptoms in university students. Methods: A cross-sectional study was conducted in Albania, Brazil, Germany, Italy, Malaysia Oman, South Korea, Switzerland, Taiwan and the USA in 2018/2019. Data were obtained through self-administered questionnaire, including questions on sociodemographic characteristics and depressive symptoms. The BDI-S was used to assess the presence of depressive symptoms. Multilevel analyses were conducted to assess the relationship between social capital and depressive, adjusting for individual covariates (e.g. perceived stress and health behaviours) and country-level characteristics (e.g. democracy type). Results: A total 3894 students participated. Out of all participants almost 47% presented clinically relevant depressive symptoms. The prevalence of depressive symptoms was highest among students identifying as other than male or female (48.7%), among students with low socioeconomic status (59.5%) and among students with low levels of cognitive (65.3%) and behavioural social capital (57.0%). Even after adjustment in multilevel logistic regression analyses, depressive symptoms remained significantly associated with low levels of cognitive social capital (OR = 1.49, 95% CI: 1.06 to 2.10) and low level of behavioural social capital (OR = 1.36, 95% CI: 1.08 to 1.71). Conclusions: Social capital may play an important role in mental health problems in the university setting. The study identified significant opportunities for future research and health promotion strategies among students. Key messages: Key factors associated with depressive symptoms among university students were low levels of behavioural and cognitive social capital. Health promotion programs targeting young persons with depressive symptoms should include effective components of social epidemiology such as social capital.